Evaluation of IL-17A and IL-17F Gene Expression in Peripheral Blood Mononuclear Cells in Different Clinical Stages of Chronic Hepatitis B Infection in an Iranian Population - Kolagar, Tannaz Akbari; Mohebbi, Seyed Reza; Ashrafi, Fatemeh; Shoraka, Shahrzad; Aghdaei, Hamid Asadzadeh; Zali, Mohammad Reza (Makara Journal of Technology, 2020)
Hepatitis B virus (HBV) infection is one of the main causes of liver damage, which can also lead to chronic hepatitis B (CHB) infection. More than 240 million individuals worldwide are chronic carriers of HBV. Among individuals with CHB who are untreated, approximately 15% – 40% will progress to liver cirrhosis or cancer. The interactions between HBV and host immune response play significant roles in the progression of CHB. CHB can be generally divided into four different clinical phases: immune tolerance (IT), immune clearance, inactive carrier, and Hepatitis B surface antigen (HBsAg)-negative reactivation phase (ENEG). Many studies showed that interleukins play important roles in anti-viral immunity and pathogenesis of chronic hepatitis. However, the relations between clinical phases of CHB and host immune transcriptome remain unclear. In this study, we aimed to investigate the expression of interleukin-17A (IL-17A) and IL-17F genes in the peripheral blood mononuclear cells (PBMCs) of patients with CHB through different clinical stages. Results were compared with the control group, which comprised individuals with no history of pre-existing medical conditions. This case–control study was carried out on 32 patients with CHB as the case group and 32 healthy individuals as the control group. According to clinical data, CHB cases were divided into two groups: active (n = 22) and inactive (n = 11). PBMC samples were obtained from all groups. After total RNA extraction and cDNA synthesis, real-time PCR was used to determine IL-17A and IL-17F expression levels. The results were analyzed by REST software, SPSS, and GraphPad Prism. The IL-17A and IL-17F gene expression levels were observed to be significantly higher in the CHB group than in the control group (IL-17A: P = 0.0013; IL-17F: P = 0.0103). The active phase group (including IT, clearance, and reactivation samples) significantly increased in comparison with the inactive phase (IL-17A: P = 0.000; IL-17F: P = 0.000). The study suggests that IL-17A and IL-17F do not only activate inflammation but are also involved in HBV-related disease progression and chronicity. Thus, mRNA levels of IL-17A and IL-17F could be used as a biomarker to diagnose CHB infection and distinguish between the active CHB phase from the inactive phase.